2021
DOI: 10.1109/access.2021.3078609
|View full text |Cite
|
Sign up to set email alerts
|

Elastic Damping Mechanism Optimization by Indefinite Lagrange Multipliers

Abstract: The current paper has presented the study on theoretical dependences of the optimization parameter (the degree of transmission transparency) on the design factors of elastic-damping mechanism (EDM) in the transmission for tractors of small traction class (14 kN). The purpose of the study was to obtain a unified functional relationship that integrates early study results. The determination of a unified function was based on reaching a compromise by the method of indefinite Lagrange multipliers. With the help of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…2222440, 2299135, 2398147, 2739100, etc.). His operation is described in detail in the literature [2,3,9,10,11].…”
Section: Results Of the Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…2222440, 2299135, 2398147, 2739100, etc.). His operation is described in detail in the literature [2,3,9,10,11].…”
Section: Results Of the Researchmentioning
confidence: 99%
“…The data of the conducted operational tests, which were carried out on plowing, continuous cultivation and sowing, showed that the studied EDM with optimal parameters [9][10][11], located in the power transmission of the 1.4 drawbar category MPT at the sufficiently high level provides protection for all components links of the MTU from fluctuations of external and internal links, which has a positive effect on the dynamic processes that occur in all elements of the MTU [2-8]. So, for example, as a result of testing an plowing MTU in the field, it was found that the application of EDM into the power transmission of the 1.4 drawbar category mobile power tool helps to reduce the amplitude of the hook force fluctuations compared to the serial version to 15 ... 20%.…”
Section: Results Of the Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…For this, the existing mechanisms need to be considered. Also, it need to be investigated whether subsystems aside from the ones in sensitivity index Consider what is included should take Next the dimensions, specificity and significance of the sub-ecosystems to Explore the marine environment want It is E. G. should be considered be given to Species richness and specialty are endangered Look after the creatures Overall, motivation-effect Relationships are absolutely subtle mission [11]. Environmental Impact Assessment in Colombia these are the guidelines earlier in the article, Columbia Importance of reading we discussed about hints when it comes to their cutting-edge boundaries for treating and handling uncertainty.…”
Section: Environmental Impact Assessmentmentioning
confidence: 99%
“…Often these quality criteria are contradictory. After all, the main problem in solving the multicriterial problem of evaluating the effectiveness of the RMES is that many quality criteria cannot be formalized, i.e., it is not always possible to establish the mathematical dependencies of these quality criteria on the varied parameters [8]. In this regard, it is proposed to solve this problem, including using the known expert methods of assessing the weight of each quality criterion and functional limitations [9].…”
Section: Introductionmentioning
confidence: 99%